Clinical effectiveness of ropinirole combined with hemodiafiltration for restless legs syndrome in uremic patients - SHAO Ning; SUN Zhi-hua; LIU Lin-wei; JIN Wen-min; YUAN Ge (Linchuang shenzangbing zazhi)
Objective To investigate the effectiveness of ropinirole combined with hemodiafiltration for restless legs syndrome in uremic patients. Methods Fifty patients with restless leg syndrome were divided into control group and experimental group by simple random method. The control group was given routine hemodialysis combined with ropinirole（ 0.25 mg/day）. The experimental group was treated with hemodialysis filtration combined with ropinirole（ 0.25 mg/day） for 12 weeks. The changes of restlessness,depression,sleep quality and quality of life scores and the changes of total parathyroid hormone and β2-microglobulin in serum were observed before and after treatment. Results After 12 weeks of treatment,the severity score of the restless leg,depression score,and sleep quality score. in the control group and the experimental group was significantly lower than those before treatment（ P < 0.05）,and those in the experimental group decreased more significantly than in the control group（ P < 0.05）. The quality of life scores in the control group and the experimental group increased significantly,and after treatment,and those in the experimental group were significantly higher than in the control group（ P < 0.05）. After dialysis,the total parathyroid hormone and beta 2-microglobulin content in the experimental group were significantly lower than those in the control group（ P < 0.05）. There was no significant difference in serum creatinine and hemoglobin levels before and after dialysis in two groups（ P > 0.05）. Conclusions The combination ofropinirole and hemodiafiltration has obvious effect on restless legs syndrome in hemodialysis patients.